(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
The hymenolepiosis by Hymenolepis nana is a major public health problem in developing countries, and the commercial drugs against this parasitosis are not enough effective. The combination of antiparasitic and antioxidant agents has improved the treatment of some parasitoses. Thus, the development of new cestocidal and antioxidant agents to treat the hymenolepiosis cases is important. In the present study, four hydroxy- and four dihydroxy-chalcones were synthesized using the catalyst boron trifluoride diethyl etherate (BF3•OEt2). The antioxidant activity and antiparasitic against H. nana of chalcones were tested, as well as the toxicity by the brine shrimp lethality bioassay and the method of Lorke. The antioxidant activity was measured by three radical scavenging assays: 2,2’-azino-bis-3-ethylbenzothiazoline-6- sulphonic acid (ABTS), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP). The hydroxyl substitution pattern (number and position), mainly in ring B, was responsible for the chalcone antiparasitic activity. At least one meta or para hydroxyl group in ring B was essential for activity of the synthetic chalcones against H. nana; The time taken for the parasite to die by the 3b and 3e chalcones (20 mg/mL) treatment was up to six times lower than the control drug Praziquantel. On the other hand, chalcones with catechol structure in ring B (3g and 3h) showed the highest antioxidant values. The toxicity evaluations suggests that synthetic hydroxychalcones with cestocidal (3b and 3e) and antioxidant (3g and 3h) activities are safe compounds and potential in vivo agents to treat this parasitosis.